Power And City Governance : Comparative Perspectives on Urban Development - DiGaetano, Alan (Book collections on Project MUSE., 1999)
This book develops a new way of comparing and understanding urban politics across national borders. The authors' approach, called "modes of governance," emphasizes governing alignments and their agendas. Applying this perspective to Boston and Detroit in the United States and Birmingham and Bristol in England, the authors compare the effects of postindustrial and urban political transformations, and link these to trends in the wider political economy.